The securitization markets handbook : structures and dynamics of mortgage- and asset-backed securities - Stone, Charles A. (Charles Austin) (Bloomberg Financial., 2005)
Noted experts Charles Stone and Anne Zissu provide an enlightening overview of how securitization works and explain how future cash flows from various asset classes from credit card receipts to mortgage payments can be packaged into bond-like products and sold to investors.